SUHU PENYIMPANAN DAN KULIT BIJI TERHADAP KADAR PURIN BIJI MELINJO - Rostiati Rostiati (Agroland: Jurnal Ilmu-ilmu Pertanian, 2013)
The objective of this research was to determine the content of purine and changes of melinjo seed quality under different storage temperatures and seed skin of melinjo. This research was conducted for one year in Laboratory of Food Microbiology, Laboratory of Nutrition and Chemistry of Animal Husbandry and Fishery Faculty, and Laboratory of Math and Natural Science Faculty of UNPAD. Two factors were studied using a Completely Randomized design. The first factor was storage temperature consisted of two levels (T1=5ºC and T2= 27ºC) and the second factor was seed skin consisted of two levels (B1 = with skin and B2 = without skin). Each treatment was repeated  five times, so there were 20 treatments in total. The lowest purine substances were found in  the T1B2 treatment with adenine substance ranging from 5.00-5.38 % and guanine 5.11-5.47%.    The changing in quality was more rapid under room temperature storage than under cold storage. Key Words : Melinjo seed, purine, storage temperature.